Functioning and Transformation of the Law of Vowel Harmony in Turkic Languages - Musayeva, Sevindj Gudrat; Moydinova, Elmira Kamariddinovna (The Lingua Spectrum, 2026)
This article examines changes in the application of the law of vowel harmony in Turkic languages. Particular attention is paid to the reasons for the weakening of this phonological phenomenon in the Uzbek language, caused both by internal linguistic processes and by external sociocultural influences, including language policy and contacts with non-related languages such as Persian and Russian. The study analyzes the historical functioning of vowel harmony as a key phonological and morphological principle of Turkic languages, its evolution, and differences in contemporary language practice, including examples from Uzbek, Kyrgyz, and Turkmen. In addition, dialectal variations, their influence on the phonetic structure, and the preservation of vowel harmony are discussed. The conclusion emphasizes that vowel harmony functions not only as a phonetic phenomenon but also as an important element of the typological, historical, and functional development of Turkic languages, requiring further linguistic research.